The Revival of Hadith Study in Modern Time - Noor, Umar Muhammad
Hadith study has undergone an irreversible decline for centuries before reaching its lowest point in the 16th century. But after more than five centuries of stagnation, it reemerges until it reaches its tipping point in the middle of the 20th century. Contemporary scholars often refer to the phenomenon as “the revival of hadith (al-nahda al-hadithiyya)” which manifested in many forms. This paper provides a preliminary study that seeks to investigate and examine the main factors behind the revival of hadith study in modern time. It will elaborate on how and why hadith study successfully recaptured the attention of Islamic scholars after centuries of desertion. For that purpose, data has been collected from various historical literature and biographical dictionaries then analyzed qualitatively. The study finds that the revival of hadith study in modern time is caused by the accumulation of both internal and external factors. Three of which are worth in-depth analysis, namely the influence of reformist idea to liberate Muslim world from the state of ignorance and foreign occupation, the acceptance of printing press after centuries of rejection that leads to the rise of the Islamic book industry, and the need to repudiate destructive views on hadith offered by western orientalist that opposes the traditional stance.